Strategi Pemasaran Produk Sayur Hindroponik “Mount Harvest” Di PT Anugerah Bumi Trawas Surabaya - Anky Fibrianti; Harsono Teguh S; Achmad Daengs GS (Jurnal Pengabdian Masyarakat, 2024)
The agricultural sector in Indonesia is an important sector in national economic growth. Most of Indonesia's population lives in rural areas and more than half of the population depends on the agricultural sector for their living. The development of the agricultural sector includes not only food crop commodities, but also plantation and horticultural crops. Horticultural commodities have high economic value, so that horticultural agribusiness (fruit, vegetables, floriculture and medicinal plants) can be a source of income for the community and farmers, both small, medium and large scale. Vegetables are the main food requirement after rice. Hydroponic vegetables are relatively more expensive because the process is not natural or in other words requires technology. So, the growing process is also much faster than organic vegetables. The advantages of hydroponic vegetables are that they are more hygienic, safer to consume, the vegetables are crisper, the higher water content can dissolve fat more effectively, the skin will be better nourished if consumed regularly, reduces triglyceride levels thereby preventing the risk of high cholesterol. Therefore, this is able to attract the attention of consumers to make it suitable for consumption. Changes in people's lifestyles form a new lifestyle, namely a healthy lifestyle. People's lifestyles reflect consumption patterns, so a healthy lifestyle makes people switch to consuming hydroponic vegetables which are considered healthier. Marketing of hydroponic agricultural products in Indonesia is quite rapid, this can be seen from the development with the increasing number of hydroponic agricultural products being sold in outlets. and large supermarkets in Indonesia, including hydroponic vegetables. Marketing of hydroponic vegetables is important to pay attention to, because it involves fulfilling consumer demand for food needs.